Comparison of original and washed pure sugar cane bagasse ashes as supplementary cementing materials. (22nd February 2021) - Lyra, Gabriela Pitolli; Borrachero, María Victoria; Soriano, Lourdes; Payá, Jordi; Rossignolo, João Adriano
Graphical abstract: Highlights: Reactivity of original and washed pure sugar cane bagasse ashes (SCBA) was compared. SCBA washing removes the potassium salts and increases SiO2 percentage in the ash. Washed SCBA (SCBA-W) had 50.2% SiO2, much higher than that for SCBA (13.9%). SCBA-W fixed 90% of calcium hydroxide in a 1:1 paste after 28 curing days at 20 °C. Abstract: The objective of this study was to evaluate the effects of potassium extraction on the pozzolanicity of sugar cane bagasse ash (SCBA), with the aim of producing reactive ash for use in cementitious composites. The sugar cane bagasse ashes were produced at 600 °C for 60 min, with a heating rate of 4 °C/min. The ashes were then ground and washed for potassium extraction. In order to assess the ash behaviour before and after potassium extraction, the following procedures were performed: energy-dispersive spectroscopy (EDS), loss on ignition (LOI), particle size distribution, x-ray powder diffraction (XRD), x-ray diffraction in calcium hydroxide paste, analysis of lime fixation by thermogravimetry, and evaluation of pozzolanic reactivity analyses. Results show that the extraction of potassium, increases the concentration of silica causing a greater pozzolanic reactivity of the ashes.